Konvergensi Media Penyiaran dan Media Sosial dalam Distribusi Informasi Publik - Elyanida, Icha; Alvareta, Bagas (Indonesian Journal of Research and Service Studies, 2024)
This study examines media convergence between broadcast media and social media in the distribution of public information in the digital era. The aim of the research is to analyze changes in information distribution patterns resulting from the integration of both media systems and their impact on the speed, reach, and credibility of public information. The method used is a library research approach with a descriptive qualitative design, based on the review of relevant literature from books, journals, and previous studies. Data analysis was conducted using content analysis techniques to identify patterns and relationships within the phenomenon of media convergence. The findings indicate that media convergence creates a hybrid communication system that accelerates information dissemination and expands public reach, while also generating challenges such as misinformation and reduced information quality control. In addition, audiences play an active role as information producers within the digital ecosystem. In conclusion, media convergence significantly transforms public communication into a more participatory system, while requiring stronger media literacy and information control to maintain information credibility.